Deformation Analysis of Surrounding Rock of Deep Roadway by the Fluid Structure Coupling Model with MIDAS-GTS. (16th March 2022) - Jiang, Jun; Hou, Zhengmeng; Hou, Kepeng; Lu, Yongfeng; Sun, Huafen; Niu, Xiangdong
Abstract : In order to verify the universal applicability of the fluid structure coupling model to the analysis requirements of deep tunnels under the MIDAS-GTS geotechnical simulation environment, the study, together with several mining enterprises, carried out verification and analysis on the measured data of 107 deep tunnels in recent years. The reference group selects the mean value of the analysis results generated by the analysis model using the preferred nonfluid structure coupling model in the MIDAS-GTS environment. Finally, it is confirmed that the fluid structure coupling model group data have significant advantages over the reference group data within the buried depth of 550 ∼ 1450 m and the tunnel cross-sectional area of 45 ∼ 102 m 2 . Finally, it is considered that the fluid structure coupling model has universal applicability within the analysis range. It is suggested that, in the future work, for example, when the tunnel construction project within the above analysis scope needs to carry out the simulation analysis of roof displacement and anchor bolt tension, the fluid structure coupling model should be directly selected as the analysis model.